2022
DOI: 10.1111/ajr.12861
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation in rural and remote areas of North Queensland: How well are we doing?

Abstract: Objective: To address access to cardiac rehabilitation (CR) for people in R&R areas, this research aimed to investigate: (1) post discharge systems and support for people returning home from hospital following treatment for heart disease (HD). ( 2) propose changes to improve access to CR in R&R areas of NQ.Setting: Four focus communities in R&R areas of NQ.Participants: Focus communities' health staff (resident/visiting) (57), community leaders (10) and community residents (44), discharged from hospital in pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 24 publications
(63 reference statements)
0
36
0
Order By: Relevance
“…Several recent research studies contribute to, and provide recommendations, for improving access and attendance to CR for people who live in R&R areas 8,9,14 . These studies include an integrative literature review that demonstrates a lack of understanding of CR, inflexible services, low referrals and attendance, 8 all underpinned by a weak systematic policy‐driven approach.…”
Section: How To Improve Access To Cardiac Rehabilitation For People I...mentioning
confidence: 99%
See 4 more Smart Citations
“…Several recent research studies contribute to, and provide recommendations, for improving access and attendance to CR for people who live in R&R areas 8,9,14 . These studies include an integrative literature review that demonstrates a lack of understanding of CR, inflexible services, low referrals and attendance, 8 all underpinned by a weak systematic policy‐driven approach.…”
Section: How To Improve Access To Cardiac Rehabilitation For People I...mentioning
confidence: 99%
“…Also, referral rates to home‐based telephone support CR (Coaching on Achieving Cardiovascular Health [COACH]) were found to be low in NQ: 4%–20% 16 . To compound this, a community study on provision and access to CR in R&R areas of NQ demonstrated that Aboriginal and Torres Strait Islander peoples prefer face‐to‐face communication with someone they trust 9 . Also, the term CR was found to be confusing as it was linked to centre‐based care including gym, learning to walk poststroke, or hip replacement, or drug and alcohol programs 9 .…”
Section: How To Improve Access To Cardiac Rehabilitation For People I...mentioning
confidence: 99%
See 3 more Smart Citations